2023
DOI: 10.1021/acs.chemmater.3c00638
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Chemistry of Colloidal Nanocrystals Capped by Organic Ligands

Abstract: Nanocrystal surface chemistry is a pivotal element in the synthesis and application of nanocrystals. This perspective focuses on colloidal nanocrystals, capped with organic ligands. We start with insights into a workhorse characterization technique: solution nuclear magnetic resonance (NMR) spectroscopy. We then discuss the different models used to conceptualize nanocrystal surface chemistry and how the classification of binding motifs helps in the prediction of surface reactions. The thermodynamics and kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…De Roo suggests that this coordination can lead to changes in the peak width of NMR spectra, as seen in the case of CdSe nanocrystals capped with oleate ligand. 59 De Roo further explains that depending upon the size of the ligand and the nanomaterial, it might become hard to detect the attached ligand by NMR. 60,61 As the NS are large in lateral dimensions and also provide a large surface area, in our results we too observe something similar; the peak around 8 ppm for m-NS has almost become imperceptible, although the other peaks are relatively easy to observe; this suggests that this particular enediol group is closest to the NS surface and the chemical interaction happens through this group.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…De Roo suggests that this coordination can lead to changes in the peak width of NMR spectra, as seen in the case of CdSe nanocrystals capped with oleate ligand. 59 De Roo further explains that depending upon the size of the ligand and the nanomaterial, it might become hard to detect the attached ligand by NMR. 60,61 As the NS are large in lateral dimensions and also provide a large surface area, in our results we too observe something similar; the peak around 8 ppm for m-NS has almost become imperceptible, although the other peaks are relatively easy to observe; this suggests that this particular enediol group is closest to the NS surface and the chemical interaction happens through this group.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…S2†), which implies a surface-bound structure. 30 EG was introduced in the synthesis as a reagent, solvent and also protecting agent to stabilize the product. The EG ligands were chemically adsorbed, as they cannot be removed through repeated washing.…”
Section: Resultsmentioning
confidence: 99%
“…Recent detailed studies of organic ligands have revealed that a slight difference in the molecular structure of aliphatic ligands significantly affects the dispersibility of the NCs. 10–13 Moreover, it has also been reported that the dispersibility and emission properties of NCs are altered by changing the primary, secondary, and tertiary structures of the phosphonic acids and thiols. 14 However, there are few examples that reveal the effect of the molecular structure of alkyl ligands on the excited-state dynamics of NCs.…”
Section: Introductionmentioning
confidence: 99%